Response of Fibroblastic Rheumatism to Infliximab - Ricardo Romiti; Mauricio Levy Neto; Marcello Menta Simonsen Nico (Dermatology Research and Practice)
Onset is usually sudden with symmetrical articular involvement of both small and large joints, occurrence of solid skin nodules, and rapid progression. Treatment is generally unrewarding. Here we report a severe and disabling case of FR responding favorably to infliximab therapy. After 32 weeks of continuous treatment, skin lesions dramatically improved and arthropathy partially regressed.